Dukungan keluarga sebagai faktor penting dalam kepatuhan minum obat pada pasien tuberkulosis paru - Putri, Meilisa Hidayah (Wellness And Healthy Magazine, 2020)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis, which can attack various organs, especially the lungs. TB treatment can be given in 2 stages, the intensive phase 2 months of treatment and the next stage 4-6 months later. Non-adherence of TB patients to treatment at a health care facility regularly becomes an obstacle in achieving recovery and may increase the risk of morbidity, mortality, and drug resistance in both TB patients and the wider community. WHO applies the Direct Observed Treatment Short Course (DOTS) strategy in the management of TB patients to ensure that patients swallow the drug under direct supervision by a Drug Supervisor (PMO). In this case the family can act as a PMO and provide support to TB patients so that it can be an important factor in tuberculosis treatment adherence. Several studies have found a relationship of family social support and medication adherence. The family needs to provide positive support to involve the family as a supporter of treatment so that there is cooperation in monitoring the treatment between the officers and family members who are sick.